Spectrum Sensing in Cognitive Radio Networks Using 5G Technology - Sunil U. Nyati (International Journal of Intelligent Systems and Applications in Engineering, 2024)
With rapid evolution in wireless communication technologies, Cognitive Radio Vehicular Networks (CR-VNs) have emerged and are being developed, by integrating cognitive radio techniques with vehicular networking systems, for better spectrum utilization and network performance. Besides that, 5G technologies can achieve their goal using CR-VNs with possible improvements in vehicular communication systems, higher data rates, low latency, and improved reliability in vehicular environments. This paper takes the idea of Cognitive Radio in Vehicular Networks using 5G technology through integration, benefits, challenges, and future developments which it may face. Then, the role of CR on dynamic spectrum management, spectrum sensing, and coexistence with other wireless technologies about vehicular networks, also what impact 5G can have on CR-VNs. Finally, identify areas of research that might make a difference in bringing about advancements in CR-VNs in the context of 5G.